Pengaruh Permainan Tradisional Gobak Sodor Terhadap Peningkatan Kemampuan Motorik Kasar Pada Anak Usia 10-12 Tahun - Naura Anisa Salsabila; Mokhamad Nur Bawono; Roy Januardi Irawan; Noortje Anita Kumaat (Lembaga Pengembangan Kinerja Dosen, 2025)
The method used is a quasi-experimental design with a one-group pretest-posttest approach. The sample consisted of 24 students, comprising 14 students from grade IV and 10 students from grade V. Data were collected through a 30-meter sprint test, zigzag running, throwing, standing on one leg, and standing long jump, both before and after the treatment involving the Gobak Sodor game. Based on the results in the ANOVA table for pretest and posttest, With a significance value of 0.000 (p < 0.05), the difference between the scores before and after the therapy was extremely significant. This suggests that the therapy significantly affected the outcomes that were measured. According to these results, fourth and fifth grade students at SDN Lidah Wetan 4 greatly enhance their gross motor abilities when the traditional Gobak Sodor game is used. The game has proven effective in enhancing students’ speed, agility, leg muscle strength, and balance. Therefore, Gobak Sodor can be considered an engaging and enjoyable alternative physical activity in physical education classes, while also supporting the optimal physical development of children.